Teachers Roles in Increasing Students' Language Ability Through Writing Poetry Learning in Elementary School - Nurika Irma, Cintya; Varahdillah Sandi, Noviea; Syahdilla, Sidna; Febriani Adha Atqiya, Annisa (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Writing poetry is part of appreciating poetry taught to elementary school students as a product production stage that requires language skills and the teacher's role in the learning process. This study aims to describe and explain the teacher's role in improving students' language skills through learning to write poetry in elementary schools. This research includes library research with data collection through reading and correlating relevant literature in books, journals, and proceedings. The method used is the descriptive analysis method. Data reduction, data presentation, and conclusion were carried out using the data analysis model of Miles & Huberman as a data analysis technique. The results of the study show that the teacher's role as (1) a learning manager includes increasing student learning interest, selecting material, the accuracy of learning models, creating a comfortable learning atmosphere, and communication skills, (2) learning resources in mastering the material and literacy skills, (3) facilitators who assist students in learning, (4) demonstrators who show real action of what is being learned, (5) motivators and innovators as high motivation to learn by involving students' experiences in learning material, (6) trainers played by teachers in practicing activities that have been learned through practice, and (7) the teacher carries out the evaluator to find out the achievement of the learning carried out and the recommendations needed in learning to write poetry in elementary schools.